A Highly Stretchable Capacitive‐Based Strain Sensor Based on Metal Deposition and Laser Rastering. Issue 9 (4th July 2017) - Atalay, Ozgur; Atalay, Asli; Gafford, Joshua; Wang, Hongqiang; Wood, Robert; Walsh, Conor
Abstract : Wearable sensing technology is an emerging area and can be utilized for human motion monitoring, physiology monitoring, and human–machine interaction. In this paper, a new manufacturing approach is presented to create highly stretchable and soft capacitance‐based strain sensors. This involves a rapid surface modification technique based on direct‐write laser rastering to create microstructured surfaces on prestrained elastomeric sheets. Then, to impart conductivity, sputtering technology is utilized to deposit aluminum and silver metal layers on the bottom and top surfaces of the elastomer sheet, creating a soft capacitor. During benchtop characterization of the sensors, this study demonstrates that the fabricated electrodes maintain their electrical conductivity up to the 250% strain, and the sensor shows a linear and repeatable output up to 85% strain. Finally, their potential is demonstrated for monitoring human motion and respiration through their integration into a wearable arm sleeve and a thoracic belt, respectively. Abstract : A new process for micrometer‐scale fabrication of buckled surfaces within thin metal films deposited onto elastomeric substrates for the development of capacitance‐based soft strain sensors is presented. The micropatterned surface is defined by a combination of direct‐write laser rastering and biaxial stretching. To impart conductivity, sputtering technology is utilized to deposit metal layers on the bottom and top surfaces of the elastomer.